2020
DOI: 10.1093/noajnl/vdaa016
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and histopathologic correlates of plasma cell-free DNA concentration and circulating tumor DNA in adult patients with newly diagnosed glioblastoma

Abstract: Background Plasma cell-free DNA (cfDNA) concentration is lower in glioblastoma (GBM) compared to other solid tumors, which can lead to low circulating tumor DNA (ctDNA) detection. In this study, we investigated the relationship between multimodality magnetic resonance imaging (MRI) and histopathologic features with plasma cfDNA concentration and ctDNA detection in patients with treatment-naive GBM. Methods We analyzed plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Moreover, the interest of cfDNA as a reflection of tumor burden was previously reported in a series showing that its level may correlate with radiological parameters. Taken together, these findings support the hypothesis that cfDNA is released from the vascularized part of the tumor [ 20 ] and that this marker might be a useful tool for disease monitoring in the TMZ maintenance phase.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the interest of cfDNA as a reflection of tumor burden was previously reported in a series showing that its level may correlate with radiological parameters. Taken together, these findings support the hypothesis that cfDNA is released from the vascularized part of the tumor [ 20 ] and that this marker might be a useful tool for disease monitoring in the TMZ maintenance phase.…”
Section: Discussionsupporting
confidence: 84%
“…First, it has been shown that total number of cfDNA molecules can be used as diagnostic marker to differentiate between glioma patients and controls (163,164), tumor type differentiating marker (163), tumor progression marker (165), and prognostic marker (164). However, it remains unclear whether total cfDNA can also be used as a marker to estimate and monitor tumor burden (164)(165)(166). Furthermore, mutations and copy number variations in cfDNA can also be utilized to differentiate between glioma patients and controls (164,(166)(167)(168)(169)(170).…”
Section: Cell-free Dnamentioning
confidence: 99%
“…However, it remains unclear whether total cfDNA can also be used as a marker to estimate and monitor tumor burden (164)(165)(166). Furthermore, mutations and copy number variations in cfDNA can also be utilized to differentiate between glioma patients and controls (164,(166)(167)(168)(169)(170). Diagnostic sensitivities ranged from 50% to near perfect accuracies.…”
Section: Cell-free Dnamentioning
confidence: 99%
“…The overall load of cfDNA molecules in plasma (or other bio-fluids) from patients with brain tumours can be recovered quickly and at minimal cost (via spectrofluorometer methods or PCR quantification) and has recently regained interest [15]. Multiple studies have explored the difference in concentration of cfDNA between various types of gliomas and healthy controls, alone or in combination with other methods [16][17][18]. In a prospective study, glioma patients had higher plasma cfDNA concentration than age-matched healthy controls prior to initial surgery (mean 13.4 vs. 6.7 ng/mL, respectively) and this correlated with tumour burden on preirradiation MRI [16].…”
Section: The Concentration In Plasma Cfdna Can Be Increased For Gliomasmentioning
confidence: 99%